User Acceptance Analysis of the BRImo Mbanking Application using the UTAUT and TPB Methods - Winata, Rahmad Waviq; Fronita, Mona; Angraini, Angraini; Megawati, Megawati (Sistemasi: Jurnal Sistem Informasi, 2025)
The advancement of digital technology has revolutionized financial services through the development of mobile banking applications such as BRImo. This study aims to analyze user acceptance of Bank Rakyat Indonesia’s BRImo mobile banking application by integrating two theoretical approaches: the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB). The core issue addressed is that despite BRImo being one of the most popular mobile banking applications in Indonesia, various user complaints still persist, potentially affecting its acceptance level. Identified problems include technical issues such as account blocking, login errors, and undelivered transaction notifications. This research employs a quantitative approach through the distribution of Likert-scale questionnaires to active university students in Pekanbaru who use the BRImo application. The results show that the model explains 20.0% of the variance in behavioral intention (R² = 0.200) and 24.3% of the variance in actual use behavior (R² = 0.243). Of the twelve proposed hypotheses, only three relationships were found to be significant: Attitude Toward Behavior on Behavioral Intention, Facilitating Conditions on Use Behavior, and Perceived Behavioral Control on Use Behavior. Conversely, variables such as Performance Expectancy, Effort Expectancy, Subjective Norms, Habit, Hedonic Motivation, and Behavioral Intention showed no significant effect. These findings indicate that internal factors such as user attitudes and behavioral control, along with external factors like the availability of support facilities, play an important role in driving actual usage behavior of the BRImo application. The study provides valuable insights, suggesting that users’ perceptions of accessibility and technical support have a stronger influence on actual usage than mere intention to use.